Doctor Who : the wheel of ice - Baxter, Stephen (Ace Books, 2013)
Aboard the Wheel, a ring of ice and steel turning around a moon of Saturn and home to a mining colony supplying a resource-hungry Earth, the Doctor, Jamie and Zoe become enmeshed in a critical situation. Suspected of sabatoge, they soon find themselves caught in a mystery that goes right back to the creation of the solar system. A mystery that could kill them all.